Novel amide-functionalized chloramphenicol base bifunctional organocatalysts for enantioselective alcoholysis of meso-cyclic anhydrides - Xu, Lingjun; Han, Shuwen; Yan, Linjie; Wang, Haifeng; Peng, Haihui; Chen, Fener (Beilstein Journal of Organic Chemistry, 2018)
A family of novel chloramphenicol base-amide organocatalysts possessing a NH functionality at C-1 position as monodentate hydrogen bond donor were developed and evaluated for enantioselective organocatalytic alcoholysis of meso-cyclic anhydrides. These structural diversified organocatalysts were found to induce high enantioselectivity in alcoholysis of anhydrides and was successfully applied to the asymmetric synthesis of (S)-GABOB.
Keywords: alcoholysis desymmetrization; bifunctional organocatalysis; chloramphenicol base